Criação e modelização de diferentes tipos de rolamentos com o uso do software de modelagem 3D fusion360 - Köhn, André Oliveira [UNESP] (2017)
The main objetive of this study was to build and create 3D models of different bearings using real data. Using the catalogue provided by the manufacturer, five different kinds of bearings were built, using the 3D Software Fusion360 by Autodesk. In this study, some characteristics and benefits that this program could bring are presented, when compared with similar softwares in the market. The main results of this study are the five guides on how to create the bearings step-by-step. These guides can be useful for creating 3D bearings with Fusion360